1999
DOI: 10.2116/analsci.15.1065
|View full text |Cite
|
Sign up to set email alerts
|

Retention Characteristics in Supercritical Fluid Chromatography and Comparison with Gas Chromatography

Abstract: A practical method for the characterization of the retention behavior in supercritical fluid chromatography (SFC) was proposed, based on the retention index. Taking easier comparison with gas chromatography (GC) into consideration, a set of six test compounds were chosen: napthalene, 1-pentadecanol, 2-pentadecanone, n-pentadecanonitrile, isoquinoline and cyclododecane. Dimethylsilicone and carbon dioxide were selected as the standard stationary phase and the standard mobile phase, respectively. Thus, the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Brantly et al, using a novel spectroscopic technique, measured the partitioning of both cosolvents (modifiers) and solutes in CO 2 -based systems in contact with polymers (7). Yaku et al compared SFC retention with GC using a McReynolds-like scale and found mobile-phase-dependent differences in the behavior of cyclic versus noncyclic compounds (8). Evans and Davis examined pressure effects on retention in reversed-phase liquid chromatography (9).…”
mentioning
confidence: 99%
“…Brantly et al, using a novel spectroscopic technique, measured the partitioning of both cosolvents (modifiers) and solutes in CO 2 -based systems in contact with polymers (7). Yaku et al compared SFC retention with GC using a McReynolds-like scale and found mobile-phase-dependent differences in the behavior of cyclic versus noncyclic compounds (8). Evans and Davis examined pressure effects on retention in reversed-phase liquid chromatography (9).…”
mentioning
confidence: 99%